Peta Pembaharuan Hukum Islam Modern:: Antara Modernisasi Hukum Islam di Saudi Arabia dan Arabisasi Hukum Islam di Indonesia - Hatta, Moh; Suhli, Suhli (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2024)
This research is motivated by the fact that Saudi Arabia, under the rule of Muhammad bin Salman, has made various revolutionary policies through Saudi Vision 2030 one by one and that Indonesia as a democratic country that is open to change is actually indicated by various efforts to change to be like Saudi Arabia, starting from culture to aspects of the state. This descriptive research with a qualitative approach produces the conclusion that behind the changes made by Saudi Arabia, it turns out there are still many who are trying so that the country of Indonesia, which is predominantly Muslim, can emulate Saudi Arabia as the direction of Muslims, including in aspects of the legal and state systems. However, efforts to implement the Islamic legal system cannot ignore the existence of beliefs that have lived in the midst of society, meaning that efforts to Arabize Indonesia need to be considered very complexly by the entire community, especially the Government, so that harmony that has been built in Indonesia today remains sustainable for the sake of the integrity of the Unitary State of the Republic of Indonesia.